2013
DOI: 10.2217/fmb.13.30
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in the Oral Pathogen Porphyromonas Gingivalis : Molecular Mechanisms and Biological Consequences

Abstract: Porphyromonas gingivalis is a Gram-negative anaerobic bacterium that colonizes the human oral cavity. It is implicated in the development of periodontitis, a chronic periodontal disease affecting half of the adult population in the USA. To survive in the oral cavity, these bacteria must colonize dental plaque biofilms in competition with other bacterial species. Long-term survival requires P. gingivalis to evade host immune responses, while simultaneously adapting to the changing physiology of the host and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
84
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 102 publications
3
84
0
5
Order By: Relevance
“…While type Ib, II and IV are most frequently associated with periodontitis [1418], type I and III are less inflammatory and are associated with strains more likely to form localized self-limiting infections [19]. It has been suggested that the fimA type II allele confers a selective advantage in the advanced disease process thus ensuring its distribution throughout the P. gingivalis population [20]. …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…While type Ib, II and IV are most frequently associated with periodontitis [1418], type I and III are less inflammatory and are associated with strains more likely to form localized self-limiting infections [19]. It has been suggested that the fimA type II allele confers a selective advantage in the advanced disease process thus ensuring its distribution throughout the P. gingivalis population [20]. …”
Section: Introductionmentioning
confidence: 99%
“…In clonal populations of bacteria, genetic diversity primarily arises by point mutations. Point mutations within open reading frames that are limited in size can occur in P. gingivalis at frequencies of 10 –9 , similar to other bacterial species such as Escherichia coli [20]. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations